The relationship between passive social network site use and sub-threshold depression among college students: a moderated mediation model - Jiangli Jiao; Xiaojuan Dong; Nuziyan Nuermaimaiti; Yi Liu (BMC Psychology)
Abstract Background Sub-threshold depression is a prevalent psychological adaptation issue among university students. Although prior research has explored the potential relationship between social media use and depressive symptoms, the findings have been inconsistent, and the potential mediating and moderating mechanisms remain unclear. This study aims to examine the relationship between passive social network site use and sub-threshold depression in college students from the perspective of the differential susceptibility to media effects model, investigating the mediating role of fear of missing out (FOMO) and the moderating role of coping styles. Methods A total of 738 students from five universities were assessed using the Passive Social Network Site Use Scale, the Center for Epidemiologic Studies Depression Scale, the Fear of Missing Out Scale, and the Simplified Coping Style Questionnaire. Descriptive statistics and correlation analysis were conducted using SPSS 26.0, and a moderated mediation model was established using Mplus 8.3. Results The findings revealed that: (1) After controlling for gender and age, passive social network site use was a significant positive predictor of sub-threshold depression; (2) FOMO mediated the relationship between passive social network site use and sub-threshold depression; (3) Negative coping styles moderated the relationship between FOMO and sub-threshold depression, such that higher levels of negative coping enhanced the predictive effect of FOMO on sub-threshold depression. Conclusion The results contribute to understanding the mechanisms through which passive social network site use influences sub-threshold depression in university students. The study suggests that reducing FOMO and enhancing students’ coping styles may help mitigate sub-threshold depression, thereby improving their psychological well-being.